Monolinguals in a multilingual landscape - Illés Éva („RIK-U” Kft., 2018)
Abstract. The point of departure for the paper is the paradox of many Hungarians failing to learn foreign languages while living in environments where they are often surrounded by languages other than their mother tongue. According to a European Commission survey (European Commission, 2012), Hungary occupies the bottom position among the 28 member states of the EU when it comes to speaking foreign languages, and every year thousands of university students are unable to obtain their degrees because university degrees in Hungary require the knowledge of a foreign language at intermediate level. One reason for these poor results might be the fact that Hungary is a monolingual country where 99% of the population speak the official language as their mother tongue (European Commission, 2012). However, in Budapest alone there were about 3.5 million tourists in 2017 https://www.quora.com/ Hungary-How-many-tourists-visited-Budapest-last-year) speaking languages other than Hungarian together with a considerable expatriate population in the capital.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: monolingual; multilingual